2015
DOI: 10.1007/s00107-015-0955-4
|View full text |Cite
|
Sign up to set email alerts
|

Fumed silica as a filler for MUPF resin in the process of manufacturing water-resistant plywood

Abstract: This work examines the effect of applying fumed silica with nanoscopic-size particles as a filling material for melamine-urea-phenol-formaldehyde (MUPF) resin in the process of manufacturing water-resistant plywood. Moreover, this paper investigates the possibility of reducing the amount of MUPF resin mixture used in the process of gluing veneer sheets. Based on the investigations into the reactivity, viscosity and durability of MUPF resin mixture containing various amounts of nanofiller, it was found that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 34 publications
4
23
0
Order By: Relevance
“…Figure 4 showed hydroxyl groups and moisture in technical and bark filler react with PF during curing process, and this process occurs at lower temperature [21]. Furthermore, Dukarska and Czarnecki [10] stated lower endothermic of glue mixtures was also caused by volatile substances in fillers. The DSC analysis also showed that glue mixture with additional BN bark cured in lower temperature than glue mixture with additional DB bark (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Figure 4 showed hydroxyl groups and moisture in technical and bark filler react with PF during curing process, and this process occurs at lower temperature [21]. Furthermore, Dukarska and Czarnecki [10] stated lower endothermic of glue mixtures was also caused by volatile substances in fillers. The DSC analysis also showed that glue mixture with additional BN bark cured in lower temperature than glue mixture with additional DB bark (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Filler can be organic or inorganic materials. Inorganic fillers that have been tried to be used for adhesive were calcium carbonate [8], glass particles [9], fumed silica [10], waste marble powder [11], and diatomite powder [12]. Organic fillers generally are biomass waste, such as walnut shell, pinenut shell, ginkgonut shell, coconut shell, periwinkle shell, palm kernel, wood flour, waste rubber, corncob residue, and wood waste ash [5,6,9,[13][14][15][16][17].…”
mentioning
confidence: 99%
“…Dukarska and Czarnecki prove that introducing fumed silica into MUPF resin, in the amount of 2 PBW/100 PBW of the adhesive reduces the value of activation energy of the cross-linking process [1]. Table 3 shows the effect of non-modified nano-SiO 2 on the reactivity of urea resin determined on the basis of activation energy measured with use of Kissinger and Ozawa methods.…”
Section: Resultsmentioning
confidence: 99%
“…So far, in the investigations on the use of nanosilica as an additive to urea-formaldehyde resin applied in production of plywood, particleboards and OSB, researchers used mainly non-modified silicas [1,5,22]. Roumeli et al show that silica non-modified with proadhesive agents, when introduced into UF resin, tends to create aggregates of various size and their number increases along with the silica content [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation